2009
DOI: 10.3748/wjg.15.264
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mechanisms underlying the pathogenesis of tropical calcific pancreatitis

Abstract: Chronic pancreatitis is known to be a heterogeneous disease with varied etiologies. Tropical calcific pancreatitis ( TCP) is a severe form of chronic pancreatitis unique to developing countries. With growing evidence of genetic factors contributing to the pathogenesis of TCP, this review is aimed at compiling the available information in this field. We also propose a two hit model to explain the sequence of events in the pathogenesis of TCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Tropical calcific pancreatitis (TCP) is an idiopathic, juvenile, nonalcoholic form of chronic pancreatitis with a unique geographical distribution, while fibro-calculous pancreatic diabetes (FCPD) is a condition, characterized by the development of diabetes secondary to TCP. A genetic etiology for TCP and FCPD has been suggested from its familial aggregation and geographical distribution (94)(95)(96). However, comprehensive screening for Reg IA gene rules out association with TCP and FCPD (97,98).…”
Section: Islet Regeneration and Diabetesmentioning
confidence: 99%
“…Tropical calcific pancreatitis (TCP) is an idiopathic, juvenile, nonalcoholic form of chronic pancreatitis with a unique geographical distribution, while fibro-calculous pancreatic diabetes (FCPD) is a condition, characterized by the development of diabetes secondary to TCP. A genetic etiology for TCP and FCPD has been suggested from its familial aggregation and geographical distribution (94)(95)(96). However, comprehensive screening for Reg IA gene rules out association with TCP and FCPD (97,98).…”
Section: Islet Regeneration and Diabetesmentioning
confidence: 99%
“…Recently, Mahurkar et al [12] have proposed a two hit model for the pathogenesis of diabetes in TCP. The first hit includes the mutation of one or more genes, resulting in the formation of supertrypsin in the acinar cell of the pancreas.…”
Section: Changing Disease Spectrummentioning
confidence: 99%
“…Studies from various parts of the Indian subcontinent have shown mutations in this gene to be associated with not only FCPD, but also other pancreatic diseases as well [26][27][28][29]. The presence of a mutation is in itself not sufficient to cause disease, requiring a ''second hit'' in the form of an environmental insult to set the pathophysiological mechanism in motion [30].…”
Section: The Cassava Hypothesismentioning
confidence: 99%